An assessment of asthma exacerbations in pediatric patients using a long-acting B2-agonist plus inhaled corticosteroid versus an inhaled corticosteroid alone - Yousif S. Alakeel; Esraa Khader; Norah Altuwayli; Shahad Alrammah; Wesam Abdel-Razaq (Elsevier, 2022)
Background: An asthma exacerbation is an anticipated sudden worsening of the disease severity, which usually does not respond to conservative therapy. The management of asthma depends on the severity of the disease symptoms, which includes an inhaled corticosteroid (ICS) and a bronchodilator. This study aimed to assess the efficacy of combining a long-acting B2-agonist (LABA) with ICS, compared to ICS alone, to reduce the incidence of asthma exacerbations in pediatric patients, diagnosed with severe persistent asthma. Methods: A retrospective analysis of the medical records was conducted for 586 children, admitted to the Emergency Department (ED) at King Abdullah Specialized Children Hospital in Riyadh, Saudi Arabia, for the management of severe persistent asthma symptoms, from January 2016 to September 2019. Results: The majority (n = 480, 81.9%) of the patients received fluticasone (Flovent)® as the standard of care ICS treatment for controlling asthma, and a small proportion (n = 106, 18.1%) were treated with a combination of LABA and ICS. A significant increase in the frequency of recurrent asthma exacerbation episodes occurred in the group receiving ICS alone (98.5%), compared to 67.0% in the combination group (p < 0.0001). Moderate to severe exacerbations were significantly higher in the ICS group compared to the combination group (95.6% versus 84.5%, respectively, p = 0.0005). Conclusions: The current results confirm the substantial efficacy of the LABA/ICS combination therapy in reducing the incidence and severity of asthma exacerbations in pediatric patients, compared to ICS alone.